Efficacy and safety of left atrial appendage closure in patients with atrial fibrillation and high thromboembolic and bleeding risk - D. V. Pevzner; A. А. Semenova; N. S. Kostritsa; I. A. Merkulova; A. L. Komarov; E. V. Merkulov (Российский кардиологический журнал, 2022)
Aim. To compare the incidence of thromboembolic and hemorrhagic events after left atrial appendage occlusion (LAAO) or without prevention of thromboembolic events (TEEs) during prospective follow-up of patients with atrial fibrillation (AF) and a high risk of ischemic stroke (IS) who have contraindications to long-term anticoagulant therapy.Material and methods. The study included 134 patients with AF, a high risk of IS, and contraindications to long-term anticoagulation. Patients were divided into 2 groups as follows: the first group included patients who underwent LAAO (n=74), while the second one — those who did not undergo any TEE prevention (n=60). The follow-up period was 3 years. The cumulative rate of all-cause mortality, IS, transient ischemic attacks (TIA), and systemic embolism (SE) was taken as the primary efficacy endpoint. The primary safety endpoint included major bleeding according to GARFIELD registry criteria.Results.  The rate of composite efficacy endpoint in the LAAO group was significantly lower than in the group without thromboembolic prophylaxis (5,2 vs 17,4 per 100 patient-years; adjusted odds ratio (OR), 4,08; 95% confidence interval (CI): 1,7-9,5; p=0,001). The rate of major bleeding was comparable in both groups (2,4 in the LAAO group vs 1,3 per 100 patient-years in the group without thromboembolic prophylaxis; adjusted OR, 0,55; 95% CI: 0,1-3,09; p=0,509). In addition, the event rate of net clinical benefit (all-cause mortality + ischemic stroke/TIA/SE + major bleeding) in the LAAO group was also significantly lower (5,9 vs 18,2 per 100 patient-years; adjusted OR, 3,0; 95% CI: 1,47-6,36; p=0,003).Conclusion. Among patients with AF and contraindications to long-term anticoagulation after 3 years of follow-up, LAAO demonstrated the significant reduction of cumulative rate of all-cause mortality and non-fatal thromboembolic events. At the same time, the frequency of major bleeding was comparable between the groups, even taking into account access-site bleeding and postoperative antithrombotic therapy (ATT)-associated bleeding in the LAAO group. Further randomized clinical trials are required to confirm these data.